Satisfaction level of students towards formal learning spaces in Universiti Teknologi Mara Perak Branch, Seri Iskandar Campus / Siti Nor Anis Ab Hadi and Thuraiya Mohd - Ab Hadi, Siti Nor Anis; Mohd, Thuraiya (2018)
Learning space is the place to study, to research, and to engage in intellectual pursuit for the betterment of mankind. The use and design of learning space in higher education (HE) is a theme that has come to the forefront of educator interest in the past few years, particularly as competition for student applications and retention issues in the university sector have increased. It has long been accepted that space quality and design impacts the educational experience and working life, and environmental factors figure substantially in terms of psychology and sociology. Researchers have found that increased satisfaction on learning space has improved students' learning performance. Thus, this research paper aims to discuss the satisfaction level of students on formal learning spaces in Universiti Teknologi MARA. The survey was conducted in Universiti Teknologi MARA (UiTM), Perak Branch, Seri Iskandar Campus, Malaysia. A questionnaire was administrated and collected from 400 students, where respondents were asked to select their preferences based on a four-point Likert scale of agreement and satisfaction. The analysis was conducted using the Statistical Package for Social Sciences (SPSS) in the form of descriptive statistics comprising mean analyses to examine the level of students' satisfactions on formal learning spaces. Findings of this research indicated that the majority of students are satisfied with the moderate level of the three (3) major aspects surveyed which are environmental, design and facilities provided. These findings will provide a significant input for Higher Education Institutions, Ministry of Education, and other stakeholders for considering implementing a strategic action plan to boost the students' satisfaction level.